New record of Rhinochimaera atlantica (Chimaeriformes: Rhinochimaeridae) spawning ground in the Gulf of Mannar along the south-east coast of India - Chembian, A John (Indian Journal of Fisheries, 2011)
The egg capsules and one embryo of Rhinochimaera atlantica were collected from the Gulf of Mannar while conducting fishery resource survey by bottom trawling. In total, 89 egg capsuleswere collected from the surveyed area (Latitude 08°51’N to 08°53"N and Longitude 78°47’E to 78°53’E ) at a depth range of 281-301 m, which indicated that this area is the probable spawning ground of the species in the Gulf of Mannar. The egg capsule measured 257 mm in total length and weighed 28 g. It was ovoid in structure with a central longitudinal hollow core surrounded on both sides with a wing-like ribbed lateral web. Embryo was spindle shaped and perfectly placed in the tubular structure of the egg capsule. The ratio of the number of unhatched egg capsules to the empty capsules indicated that, March / April may be the terminal period of incubation. Theembryo observed was in the advanced stage of release as the embryo nearly occupied the full length of central hollow core.